Nilai Budaya Islam dalam Perkembangan Industri Songket Melayu Batu Bara: Studi Desa Padang Genting Kecamatan Talawi Batu Bara - Muktarruddin, Muktarruddin; Aulia, Najwa; Nurhalizah, Nurhalizah; Sihombing, Nur Asia; Sitorus, Mujahidin Abdulhadi (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
Songket is the result of hand-woven made of varioustypes of yarn and decorated with various motifs. Songket can found in several regions in Indonesia as a type of folk craft that characterizes each region, besides that songket weaving is also one of the livelihoods of the population. The Batu Bara Malay songket woven cloth serves as a symbol and identity for the Malay community in Batu Bara. In order to collect complete information. This study uses intensive interview techniques at some time in 2023, and also conducts a literature study. This study resulted that the Malay Batu Bara songket industry can be a source of income forlocal residents and has a connection with Islamic culture in its use. Keywords : Industry, Songket, History, Islamic Cultural Values